2006
DOI: 10.1590/s0103-84782006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Componentes genéticos de médias e depressão por endogamia em populações de milho-pipoca

Abstract: Ten popcorn populations (PR 038, PR 079, RR 046, SC 016, PR 017, BRS ANGELA, SC 002, PR 009, PR 023 and SE 013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 10 publications
(17 reference statements)
8
14
0
4
Order By: Relevance
“…The dominance effect was positive for plant height and ear height, where inbreeding depression was significant, explaining the decrease in the magnitude of these variables (Table 2). These results are in accordance with reports by Scapim et al (2006). On the other hand, Simon et al (2004) found some popcorn populations with a negative dominance effect for these traits, i.e.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The dominance effect was positive for plant height and ear height, where inbreeding depression was significant, explaining the decrease in the magnitude of these variables (Table 2). These results are in accordance with reports by Scapim et al (2006). On the other hand, Simon et al (2004) found some popcorn populations with a negative dominance effect for these traits, i.e.…”
Section: Resultssupporting
confidence: 92%
“…Scapim et al (2006) also found a predominance of additive effects and 10% of inbreeding depression for plant height and ear height. In maize, the dominance effects of plant height and ear height were higher than those in popcorn (Hallauer and Miranda Filho, 1981).…”
Section: Resultsmentioning
confidence: 85%
“…Para o efeito de grupos por locais foi detectada a não significância de FM, AE e MG, indicando comportamento não diferencial dos híbridos nos dois locais de avaliação, o que é um resultado altamente interessante para o programa de melhoramento em questão. Os coeficientes de variação de todos os caracteres avaliados estão dentro dos limites aceitáveis para experimentação agrícola, conforme Scapim et al (1995).…”
Section: Resultsunclassified
“…A depressão por endogamia média foi de 6,1% para altura de planta e espiga. Scapim et al (2006) encontraram predominância de efeito aditivo e depressão por endogamia de 10% para altura de planta e espiga. Os híbridos deste estudo apresentaram alta estimativa de depressão por endogamia para MG: de 48,1% no HC10, de 36,3% no HC13 e de 39,2% no HC14; para FM, foi de 6,2% no HC15, para AP e AE, foram de 13,0% e 8,6%, respectivamente, no HC10, e de 7,7% e 9,7%, respectivamente, no HC15 (Tabela 4).…”
Section: Resultsunclassified
“…As sete cultivares de milho-pipoca são: zélia (híbrido triplo), Jade (híbrido triplo), iAC 112 (híbrido simples modificado), IAC 125 (híbrido triplo), BRS Angela (variedade), e UFVM2-Barão-Viçosa (variedade). Verificase, portanto, que apesar dos avanços o número de variedades e híbridos de linhagens comerciais de milho-pipoca, é reduzido em relação à crescente demanda pelo produto (VENDRUSCOLO et al, 2001;MATTA;ViANA, 2001;ANDRADE et al, 2002;DAROS et al, 2004;FREiTAS JúNiOR et al, 2006;SCAPiM et al, 2006;RANGEL et al, 2007;RANGEL et al, 2008;SANTOS et al, 2008;ViEiRA et al, 2009). Na Região Noroeste do Paraná existem empacotadoras que comprariam o produto se os agricultores começassem a semear em larga escala (PiNTO et al, 2007).…”
Section: Introductionunclassified